2012
DOI: 10.4103/0976-0105.103824
|View full text |Cite
|
Sign up to set email alerts
|

Improving monitoring and reporting of adverse drug reactions (ADRs) in HIV positive patients on antiretroviral therapy (ART) in Nigeria

Abstract: Under-reporting of ADR may be associated with poor knowledge, attitudes and practices to pharmacovigilance. This study evaluated knowledge, attitudes and practices of healthcare professionals about ADR monitoring and reporting following interventions. This longitudinal study included 36 healthcare professionals participating in ART program in a tertiary hospital. Interventions included group training on pharmacovigilance (PV) and provision of ADR reporting forms amongst others. Assessments were conducted at mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…10 In our study, incidence of ADRs to ART in males and females did not show any signifi cant difference (males 50.6%, females 49.4%) and CD4 count of <250 cells/μl were affected with more ADRs (65.82%) (Figure 1). A study from Kadapa, India showed the majority of ADRs were observed in males (60%) and CD4 count of <250cells/μl were affected with more ADRs.…”
mentioning
confidence: 88%
“…10 In our study, incidence of ADRs to ART in males and females did not show any signifi cant difference (males 50.6%, females 49.4%) and CD4 count of <250 cells/μl were affected with more ADRs (65.82%) (Figure 1). A study from Kadapa, India showed the majority of ADRs were observed in males (60%) and CD4 count of <250cells/μl were affected with more ADRs.…”
mentioning
confidence: 88%
“…The most common reason for excluding the records was further publication of relevant studies that suffered from insufficient data (n = 22). Moreover, seven studies were excluded because of their irrelevant outcomes [34][35][36][37][38][39][40] (Figure 1). To identify the published full-text reports of the included abstracts, the databases were searched and three full-text articles were retrieved, 2,24,41 and one paper was received along with a response from the author out of the nine communications made.…”
Section: Overviewmentioning
confidence: 99%
“…Under-reporting of ADR may be associated with poor knowledge, attitudes, and practices to pharmacovigilance. [23] In the current study, awareness about pharmacovigilance was created through regular monitoring of patients and their profiles with other HCPs, providing pamphlets, hand outs, and thank you note to the reporter. In phase-II study, most of our participants were aware of pharmacovigilance program when compared with the phase-I study.…”
Section: Discussionmentioning
confidence: 99%